Risk Factors for Mortality and Outcomes in Pediatric Acute Lung Injury/Acute Respiratory Distress Syndrome*. Issue 7 (September 2015) - Panico, Flávia F.; Troster, Eduardo J.; Oliveira, Cindy S.; Faria, Aline; Lucena, Michelle; João, Paulo R. D.; Saad, Everardo D.; Foronda, Flávia A. K.; Delgado, Artur F.; de Carvalho, Werther Brunow
Abstract : Objectives: Children admitted to PICUs often present with or develop respiratory failure that requires mechanical ventilation. We prospectively identified children admitted to three general PICUs, with the goal of identifying risk factors for mortality. Design: Prospective multicenter observational study. Setting: Three general PICUs, two in São Paulo and one in Curitiba, Brazil. Patients: Children aged between 1 month and 15 years, consecutively admitted between August 2008 and July 2010, with acute lung injury or acute respiratory distress syndrome that developed at least 12 hours after invasive or noninvasive mechanical ventilation. Interventions: None. Measurements and Main Results: We used logistic regression models to explore the relationship between death and independent variables. Of 3, 046 patients admitted to the three PICUs, 1, 658 patients underwent mechanical ventilation, and 84 fulfilled the acute lung injury/acute respiratory distress syndrome inclusion criteria and were analyzed. Nearly 60% were boys, and the median age was 31 months. Pressure control/assist control was the initial mode of mechanical ventilation in 86% of cases, and the median durations of mechanical ventilation and PICU stay were 12 and 15 days, respectively. None of the eight patients with acute lung injury died, whereas 33 of 76 of the remaining patients with acute respiratory distress syndrome died, for an overall mortality rate of 39.3% (95% CI, 28.8–50.6%). In different multivariate logistic regression model, the number of organ dysfunctions at admission, peak inspiratory pressure, airway pressure gradient on day 1, and the mean airway pressure gradient over the first 7 days of mechanical ventilation were significantly associated with mortality. Conclusion: Mortality is high in pediatric acute lung injury/acute respiratory distress syndrome. Mechanical ventilation–associated risk factors for death among such patients are potential targets for intervention.